2021
DOI: 10.1186/s40854-021-00278-6
|View full text |Cite
|
Sign up to set email alerts
|

Network DEA based on DEA-ratio

Abstract: Data envelopment analysis (DEA) is a technique to measure the performance of decision-making units (DMUs). Conventional DEA treats DMUs as black boxes and the internal structure of DMUs is ignored. Two-stage DEA models are special case network DEA models that explore the internal structures of DMUs. Most often, one output cannot be produced by certain input data and/or the data may be expressed as ratio output/input. In these cases, traditional two-stage DEA models can no longer be used. To deal with these sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…ey found that most mining companies became more efficient over time in Australia. In addition, there are many researchers have examined the efficiency performance of financial institutions based on traditional DEA [21,22]. e two-stage network was able to explain more about the variables that affect the efficiency of companies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…ey found that most mining companies became more efficient over time in Australia. In addition, there are many researchers have examined the efficiency performance of financial institutions based on traditional DEA [21,22]. e two-stage network was able to explain more about the variables that affect the efficiency of companies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Where i = 1,2,…, n; j = 1,2,…, m; S ij represents the jth input slack variable for the ith sample firm, f(Z i , β j ) represents the effect of external influencing factors on the input slack variable, u ij represents the management inefficiency term, v ij represents the random error term, u ij and is v ij mutually independent. Using the formula of Akbarian [ 22 ] to estimate management inefficiency and calculate the adjusted input slack variables, as shown in Eq ( 3 ): …”
Section: Methodsmentioning
confidence: 99%